Biometry, optical coherence tomography, and further clinical observations in Knobloch syndrome - Al Bakri, Amani (2017)
Purpose: Knobloch syndrome is a pathognomonic vitreo-retinopathy that includes zonular weakness, high myopia, and a distinct fundus appearance with tessellation out of proportion to the degree of myopia. Whether myopia in Knobloch syndrome is axial or lenticular is unclear. Also not known are the optical coherence tomography (OCT) correlates to the distinct fundus appearance. In this study we assess cycloplegic refraction, biometry, and macular spectral domain (SD) OCT in children with Knobloch syndrome. Methods: A retrospective case series of seven children (12 eyes) with Knobloch syndrome. Results: Twelve eyes with attached retinas (seven patients, aged 6–17 years old, mean 11 years) were identified, seven of which had OCT. Best-corrected vision was typically 20/300 or worse. Axial length divided by corneal radius was >3 for all eyes (3.23–3.77, mean 3.52), consistent with axial myopia, and axial lengths (26.58–30.27 mm, mean 28.16) were consistent with spherical equivalent degree of myopia (−10.00 to −18.50, mean −12) when compared to historical controls. OCT revealed lack of choriocapillaries, outer retinal disorganization, and lack of or only rudimentary foveal pit. Conclusions: Refractions and biometry in Knobloch syndrome are consistent with the myopia being axial. In addition to vitreo-retinopathy, choroidopathy is part of the phenotype and is an anatomical correlate to the distinctive fundus appearance.